Meningkatkan Keterampilan Menggambar, Menulis, dan Membaca Anak dengan Penggunaan Sandpaper Letters [Increasing Children's Drawing, Writing, and Reading Abilities with the Usage of Sandpaper Letters] - Fitavera, Ruth (Jurnal Teropong Pendidikan, 2022)
Early drawing, writing, and reading are some good aspects that can be developed to nurture children’s language acquisition from early childhood.  Environment stimulation is also one of important aspects, of which includes learning resources and teacher’s awareness of the importance of personal approach toward students. The problem that is encountered by Kindergarten 2 teachers is some students have difficulties in their early drawing, writing, and reading. This issue had brought the researcher’s attention to analyze the problem and tried to find solution, which one of them is the use of Sandpaper Letters with Montessori approach to develop early drawing, writing, and reading abilities. This research is a weak experimental research to 10 Kindergarten 2 students recommended by the homeroom teachers. The treatment used sandpaper letters with the Montessori approach for six weeks with one on one session. The result from pretest and posttest of drawing skill was N-gain 0,64 (medium), the writing skills N-gain 0,7 (high), and reading skills N-gain 0,7 (high). Based on the result, it is showed that Sandpaper letters with Montessori approach could affect the improvement of difference pace learner in early drawing, writing, and reading skills at kindergarten.